Ecosystem function of soil invertebrates and relationships of soil properties from different agriculture field in university campus and private farm in Peninsular Malaysia - Abrar S Maqtan,; Hishamuddin Omar,; Muskhazli Mustafa,; Nur Ain Izzati Mohd Zainudin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The invertebrate species play different roles above and below ground in a soil ecosystem. They are also responsible for a complex interaction, which is manifested in soils as self-organized systems of different sizes and functions. These invertebrates are sensitive to any changes in land management activities and soil physio-chemical properties. Therefore, the current study aims to examine the ecosystem functions of soil invertebrates from different agriculture fields and establish the relationships of soil physio-chemical properties. Soil samples were collected from four different fields: three are from the main campus, namely Universiti Putra Malaysia (Center of Environmental and Forensic Studies (CEFS), papaya and organic farm), and one is from Nilai, Negeri Sembilan. The soil physical properties, such as moisture, temperature, particle size, bulk density, and soil porosity, were recorded. Soil chemical properties (EC, pH, total C&N, C/N ratio, organic matter, extractable P, Ca, Mg, K, and Na, CEC) were also determined. Pitfall traps and Berlese funnel were used as sampling methods. The invertebrates were stored in 70% ethanol and identified using soil invertebrate morphological classification, which was classified based on body size and biological functional groups. Macrofauna composition in the papaya farm was abundant from other sites at 80.44%, and ecosystem engineers comprised 39.56%. By contrast, mesofauna was abundant with 43.22% in organic farms, and litter transformers were abundant in CEFS at 54.05%. Meanwhile, microfauna was high in organic farms at 2.85%. Predatory populations were also high in Nilai farm at 49.29%. The CCA analysis showed that the physical and chemical properties of soil influence soil fauna density and diversity. The present finding concludes that the activities of ecosystem functions of soil invertebrates were considerably affected by agricultural and management activities.